Thyroid hormone profile and PELOD score in children with sepsis - Agung G. Tanurahardja; Antonius H. Pudjiadi; Pramita G. Dwipoerwantoro; Aman Pulungan (Indonesian Pediatric Society Publishing House, 2014)
Background Thyroid hormonal dysfunction, also known as euthyroid sick syndrome or nonthyroidal illness, can be seen in sepsis. There have been few studies on thyroid hormone dysfunction in septic children, as well as on a relationship between their thyroid hormone profiles and pediatric logistic organ dysfunction (PELOD) scores. Procakitonin (PCT) is one of the sepsis biomarker. Objective To evaluate the thyroid hormone profile in children with sepsis as well as to assess for a correlation between the thyroid levels and PELOD scores, PCT levels, and patient outcomes. Methods This cross-sectional study included children aged 1- 18 years admitted to the pediatric intensive care unit (PICU) with a primary diagnosis of sepsis. PELOD scores and thyroid hormonal levels were assessed once during the first 24 hours after PICU admission. Results Thirty subjects were included in the study. The median values ofT3, free T4, and TSH were 45 (range 17 -133) ng/dL, 0.81 (range 0.3-1.57) ng/dL, and 1.36 (range 0.05-7.78) μIU/L, respectively. The T3, free T4, and TSH levels were decreased in 97%, 50% and 40% of the subjects. There were no significant differences between low and normal to high TSH with regards to the PELOD score (P=0.218), PCT level (P=0.694), or patient outcomes (P=0.55). The risk of death increased by 15 times among the subjects with PELOD score ~20 compared to those with PELOD score <20 (OR 15; 95%CI: 1.535 to 146.545; P=0.012). Conclusion Thyroid hormones are decreased in septic children with the majority having low T3. A high PELOD score is strongly correlated with mortality and can be used as a prognostic parameter for septic children in the PICU, but there is no correlation with decreased TSH.